2008
DOI: 10.1002/ldr.888
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lignite washery sludge on mine soil quality and poplar trees growth

Abstract: This paper outlines research on the use of lignite washery sludge as the amendment for reclamation of lignite mine soil and stimulating poplar trees growth. Sludge is characterized by high total C content ($34%) and high C/N ratio (68:1). The sludge was introduced by ploughing in, down to 20-25 cm depth, in the quantities: 0, 28, 56 and 112 t ha À1 . We have established that the N percentage in poplar leaves decreases with introducing increasing quantities of sludge into the mine soil. On the other hand, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Unweathered fly ash fly ash and mine spoil, prevent wind erosion, decrease mobility, toxicity, and dispersion of chemical elements in the surrounding environment, provide the organic substance which can bind contaminants and reduce transfer of pollutants in the food web (DŽeletović and Filipović, 1995;Pavlović et al, 2004;Djurdjević et al, 2006;Mitrović et al, 2008;DŽeletović et al, 2009;Haynes, 2009;Pandey, 2012;Maiti, 2013;Pandey et al, 2015aPandey et al, ,b, 2016aGajić et al, 2016). Therefore, ecorestoration of degraded sites is the process of renewing ecosystem stability and resilience after stress or disturbance with respect to its health, integrity and sustainability (SER, 2002) presenting a key issue in environmental science and ecological engineering.…”
Section: Parametersmentioning
confidence: 99%
“…Unweathered fly ash fly ash and mine spoil, prevent wind erosion, decrease mobility, toxicity, and dispersion of chemical elements in the surrounding environment, provide the organic substance which can bind contaminants and reduce transfer of pollutants in the food web (DŽeletović and Filipović, 1995;Pavlović et al, 2004;Djurdjević et al, 2006;Mitrović et al, 2008;DŽeletović et al, 2009;Haynes, 2009;Pandey, 2012;Maiti, 2013;Pandey et al, 2015aPandey et al, ,b, 2016aGajić et al, 2016). Therefore, ecorestoration of degraded sites is the process of renewing ecosystem stability and resilience after stress or disturbance with respect to its health, integrity and sustainability (SER, 2002) presenting a key issue in environmental science and ecological engineering.…”
Section: Parametersmentioning
confidence: 99%
“…-The use of lignite washery sludge resulted in lower leaf N content and higher levels of B and Cd. This kind of sludge did not stimulate the growth of poplars the first years after application, perhaps due to soil acidification caused by the pyrite they contained and to their limited levels of organic substances [47]. -Growth of coppiced eucalyptus (cut late in the season to stimulate growth during the next growing season) was inhibited by effluents from a food processing factory, but not in the case of non-coppiced trees, probably because of the stump waterlogging by the effluent [48].…”
Section: Impact On Tree Yield and Physiologymentioning
confidence: 94%
“…Nevertheless, agricultural utilization of sewage sludge to mudflats may contain some toxic elements (e.g., heavy metals) to plants and contaminate groundwater after leaching (McLaren, Clucas, Taylor, & Hendry, 2004;Richards, Steenhuis, Peverly, & Mcbride, 1998). Many previous studies on the use of sludge in degraded farmland (Gorbacheva, Kikuchi, & Gorbachev, 2009;Mamedov et al, 2016;Marques, Jimenez, Perez-Rodriguez, Garcia-Ormaechea, & Bienes, 2005;Ojeda, Alcaniz, & Ortiz, 2003;Sort & Alcaniz, 1996), forest (Dzeletovic, Filipovic, Stojanovic, & Lazarevic, 2009;Hueso-Gonzalez, Martinez-Murillo, & Ruiz-Sinoga, 2014), and quarry soil (Lozano, Fernandez, & Alvarez, 1999;Sort & Alcaniz, 1999) showed that farmland use of sludge could increase heavy metal uptake and accumulation in crop plants (Bozkurt & Yarilgac, 2003;Smiri, Elarbaoui, Missaoui, & Ben, 2015) and leaching loss of heavy metals in soil leachate (Cerezo, Marcos, & Rodriguez, 1999;McLaren et al, 2004;Paramasivam, Sajwan, & Alva, 2006). Transport and fate of the metals in mudflat salt-soil amended by sludge are quite different from those in farmlands due to difference in soil properties including salinity, pH, structure, microbial flora and background level of heavy metals, and so forth (Mallol, 2006;Singh & Kar, 2001).…”
Section: Introductionmentioning
confidence: 99%